Uncovering Pretend-Play and Peer Culture among Kindergarten Children: A Developmental Perspective - Firman Parlindungan; Lia Lisyati; Endah Anisa Rahma (Universitas Teuku Umar, 2019)
In this paper, we draw upon three observation data to explore the concept of pretend play and peer cultures among kindergarten children situated in a childcare center of the Midwestern area of the U.S. Framed in this study, Paley’s (1992) notion of dynamic play that exists within children that children behavior is changing over time and across ages. Pretend-play and peer culture are worth investigating to better understand children’s social development that might have implication for their success in education. Two observation data were obtained from a university-based Child Care Center, and one from an Indonesian family who have lived in the U.S. for three years. 12 children aged three to four years old and two kindergarten teachers were involved during the observation. The observations lasted for about 40 minutes. The findings suggest that the children were involved in different kinds of play: (1) spontaneous fantasy, and (2) socio-dramatic play. Spontaneous fantasy is when children are involved in a less structured play or no strict rule that governs the activity. Socio-dramatic play is kinds of play when children take agency that exist in the society, such as mothers, fathers, workers, and other adulthood. Both types of pretend play embodied shared knowledge about how to play appropriately based on the theme and plot emerged.